Softening the blow: Job retention schemes in the pandemic - Jolan Mohimont; Maite De Sola Perea; Marie-Denise Zachary (National Bank of Belgium, 2022)
We evaluate the welfare effects of the economic consequence of the COVID shock and job retention schemes (JRS) in a heterogenous agents DSGE model calibrated to the euro area. We find that the welfare cost of the COVID shock is large. Households who hold a limited stock of financial wealth and are unable to perfectly insure against shocks to their labor incomes experience larger welfare losses. JRS implemented in response to the pandemic have large favorable welfare effects and benefit all households. These gains are particularly strong for liquid-asset-poor households, especially for those that are also unemployed or furloughed. JRS bring stronger benefits in economies characterized by labor markets with low exit/entry rates from/to unemployment.
Keywords: E21; E24; E52; E62; 330; COVID-19; job retention schemes; furlough; household inequality; idiosyncratic risks; labor markets; welfare cost; DSGE